Adaptasi Psikologi Tokoh Kuramoto Hari dalam Film Kudakechiru Tokoro Wo Misete Ageru Karya Sutradara Sabu (Kajian Psikologi Sastra) - Fetiadi, Shella Silvia; Nur Ridha, Dian Annisa; Widyatwati, Ken; Suryadi, M (KIRYOKU, 2025)
This study aims to analyze developmental stages of Kuramoto Hari's character in Kudakechiru Tokoro Wo Misete Ageru in terms of Erik Erikson's personality development theory. This research is a literature study. The method used in this research is literary sociology, because the formal object in this research is related to the psychological aspects of the character. The theories used in this research are narrative structure theory and Erik Erikson's personality development theory to analyze the personality development experienced by the main character Kuramoto Hari in Kudakechiru Tokoro Wo Misete Ageru by director Sabu. Based on the analysis in this study, there are of Kuramoto Hari's personality development using Erik Erikson's theory of personality development which consists of eight stages. This movie tells the story of Kuramoto Hari's time in high school aged around 15 years old until Kuramoto Hari becomes a mother aged around 40 years old. So that the author only analyzes three stages of Erik Erikson's personality development, namely from stage five aged 12-18 years, stage six aged 18-35 years, and stage seven 35-64 years. Kuramoto Hari successfully passed all three stages.